Edible films from essential-oil-loaded nanoemulsions: Physicochemical characterization and antimicrobial properties - Acevedo-Fani A; Salvia-Trujillo L; Rojas-Graü MA; Martín-Belloso O (Massey University)
Edible films including active ingredients can be used as an alternative to preserve food products. Essential oils (EOs) exhibit antimicrobial activity against pathogenic microorganisms but their low water solubility limits the application in foods. To improve water dispersion and protect EOs from degradation, nano-sized emulsions emerge as a viable alternative. Nanoemulsions containing EOs and polysaccharides could be used to form edible films with functional properties. This study was focused on the evaluation of physical, mechanical and antimicrobial properties of alginate-based edible films formed from nanoemulsions of EOs. Nanoemulsions containing thyme (TH-EO), lemongrass (LG-EO) or sage (SG-EO) oil as dispersed phase and sodium alginate solution as continuous phase were prepared. The average droplet size of nanoemulsions was reduced after the microfluidization treatment exhibiting multimodal size distributions. The ζ-potentials of nanoemulsions were between-41mV and-70mV depending on the type of EO used. The lowest whiteness index was found in SG-EO nanoemulsions, whereas those containing TH-EO showed the highest value. Films formed from SG-EO nanoemulsions exhibited higher transparency, water vapor resistance and flexibility than films formed from TH-EO or LG-EO. Edible films containing TH-EO were those with the strongest antimicrobial effect against inoculated Escherichia coli, achieving up to 4.71Log reductions after 12h. Results obtained in the present work evidence the suitability of using nanoemulsions with active ingredients for the formation of edible films, with different physical and functional properties.
Keywords: Nanoemulsions; Microfluidization; Essential oils; Edible films; Antimicrobial activity; Sodium alginate; 0904 Chemical Engineering; 0908 Food Sciences; 0912 Materials Engineering